2009
DOI: 10.1080/01690960902981883
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of grammatical recursion in German learners of Dutch

Abstract: We examined the multilingual comprehension and learning of cross-serial and embedded constructions in Germanspeaking learners of Dutch using magnetoencephalography (MEG). In several experimental sessions, learners performed a sentence-scene matching task with Dutch sentences including two different verb orders (Dutch or German verb order). The results indicated a larger evoked response for the German order relative to the Dutch order over frontal sensors after three months, but not initially. The response impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 84 publications
3
12
1
Order By: Relevance
“…In contrast, a number of recent studies on L2 syntactic acquisition rather suggest a parallel course of behavioral and neural correlates of syntactic discrimination ability (Davidson & Indefrey, 2009, 2011. Although we do not want to deny that a certain "gut feeling" might contribute to syntactic processing in a second language, these and our results clearly show that the role of implicit knowledge is fairly limited when compared with that of subjective, but explicit, representations.…”
Section: Implications For L2 Syntactic Processing Researchcontrasting
confidence: 54%
“…In contrast, a number of recent studies on L2 syntactic acquisition rather suggest a parallel course of behavioral and neural correlates of syntactic discrimination ability (Davidson & Indefrey, 2009, 2011. Although we do not want to deny that a certain "gut feeling" might contribute to syntactic processing in a second language, these and our results clearly show that the role of implicit knowledge is fairly limited when compared with that of subjective, but explicit, representations.…”
Section: Implications For L2 Syntactic Processing Researchcontrasting
confidence: 54%
“…Based on both the behavioral results and the electrophysiological responses, we found that when a grammar rule is taught individually in an intensive training paradigm, learning can occur rapidly (within hours) and it is usually accompanied by changes in neural responses that are similar to L1-like patterns, as it has been shown in previous studies (Mueller et al, 2005, 2007, 2008; Davidson and Indefrey, 2009a,b, 2011). Nevertheless, these results differ from other studies finding that adult learners' brain responses differed from the ones of native speakers (Pakulak and Neville, 2011; Meulman et al, 2014; Díaz et al, 2016).…”
Section: Discussionsupporting
confidence: 65%
“…From previous fMRI studies we know that the localized areas have been found to be part of the language network involved in speech comprehension (Friederici, 2011). Similarly, Davidson and Indefrey (2009b) studied the MEG response to phrase-order violations in German learners of Dutch, and a source reconstruction of that activity implicated a variety of left-hemisphere perisylvian areas showing a greater amplitude response to grammatical violations after months following formal coursework. The fact that the main effect occurs on language areas could suggest that the new L2 memories are being created and embedded in regions that already process lexical and grammatical information, rather than in separate regions that are responsible for other cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations